PENGEMBANGAN MEDIA LOOSE PARTS UNTUK MENINGKATKAN HASIL BELAJAR KEMAMPUAN MEMBACA PERMULAAN SISWA SD KELAS II - Oktalita Nur Rahmawati; Lina Putriyanti; Sukamto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low level of read the beginning of class IIstudents. The type of research employed is the Research and Development (R&D)method. The purpose of this study was to implement the developed Loose Partsmedia to enhance the read the beginning abilities of second grade students atPandean Lamper 02 elementary school in Semarang and Sidoharjo 01 elementaryschool in Tegal. The development process followed the ADDIE model and OneGroup Pre-test and Post-test Design. Data analysis techniques included normalitytesting, homogeneity testing, paired sample testing, and N-gain testing. A total of47 students participated in the study, receiving both pre-test and post-test toevaluate the effectiveness of the learning intervention. The result of the N-Gainanalysis is 0,587 classified in the medium category. This showed that the appliedinstructional had a significant impact on improvement the result of studentslearning. Therefore, the Loose Parts learning media is considered a feasiblealternative to support the development of ability to read the beginning.